A modified Poisson-Boltzmann approach to homogeneous ionic solutions - Outhwaite, C.W. (Condensed Matter Physics, 2004)
The mean electrostatic potential approach to ionic solutions was initiated by the mean field work of Gouy and Chapman for inhomogeneous systems, and Debye and Huckel for bulk solutions. Any successful extension of the mean field theories requires an adequate treatment of both the exclusion volume and fluctuation terms. One such development has been the modified Poisson-Boltzmann approach. Although the bulk modified PoissonBoltzmann theory was introduced 35 years ago, only a limited amount of work has been put into its development due to the successful application of liquid state theories to ionic systems. We outline here the bulk modifi ed Poisson-Boltzmann equation, comment on some of its successes, and mention some outstanding problems. Підхід середнього електростатичного потенціалу був ініційований роботами Гуї і Чепмана для неоднорідних систем та Дебая і Гюккела для об’ємних розчинів. Будь-яке успішне розширення теорії середнього поля вимагає адекватного трактування ефектів як виключеного об’єму, так і флуктуаційних членів. Одним із них є модифікований підхід Пуассона-Больцмана. Хоча “об’ємна” модифікована теорія Пуассона-Больцмана була запропонована 35 років тому, тільки є обмежене число робіт використало її завдяки успішному застосуванню теорій рідкого стану до іонних розчинів. Тут ми викладаємо “об’ємне” модифіковане рівняння Пуассона-Больцмана, обговорюємо його переваги і згадуємо деякі найважливіші проблеми.